Children Motoric Development Through Variety of Greetings - Taat Kurnita Yeniningsih (Universitas Serambi Mekkah, 2021)
Types of greetings are the kinds of movements that result from the greeting processin the form of greetings to someone / another person which will have an impact onthe child's motoric skills from the various greeting movements. Variety of greetingsis synonymous with the diversity produced by the greeting itself, thus creatinggestures similar to greetings. The kinds of greetings referred to are in the form ofAssalamu'alaikum, movements of shaking hands, gestures of hugs and clappingmovements. The purpose of this study was to determine children's motoricdevelopment through the application of various greetings at IT Mon KutaKindergarten in Lambhuk Village, Banda Aceh. This is the qualitative research witha descriptive approach. Data collection techniques namely; through interviews andobservations. The data analysis technique in this study is a collection of data that hasbeen obtained from the results of children's observations that researchers have donesince the beginning of each aspect of research activities, the results that have beencollected are entered into the observation sheet. The results showed that thechildren's motoric development had started well. The motoric development of thechild is done through a variety of ways, namely that the child can mimic movementsand control movements. So, through various greetings activities can developchildren's motoric aspects.